2016
DOI: 10.1021/acs.energyfuels.6b00519
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Desulfurization: Fast On-Board Regeneration and the Influence of Fatty Acid Methyl Ester on Desulfurization and in Situ Regeneration Performance of a Silver-Based Adsorbent

Abstract: Adsorptive on-board desulfurization units require a high desulfurization and regeneration performance for a wide range of fuels to keep them small and ensure long maintenance intervals. A novel thermal regeneration strategy was investigated in this work, fulfilling all requirements for in situ on-board regeneration. In this strategy, a temperature-controlled flow rate (TCFR) of air was used to control the temperature inside the adsorber. With this dynamic approach, the regeneration time was reduced significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
3
12
0
Order By: Relevance
“…33 The most prominent metal ions for π-complexation are Cu(I) and Ag. 34,35 A number of research studies have been done on the modification of MOFs in order to attain the improved performances for sulfur removal. Due to its tunable chemical structure, Cu-BTC has received wide interest in the structural modification.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 The most prominent metal ions for π-complexation are Cu(I) and Ag. 34,35 A number of research studies have been done on the modification of MOFs in order to attain the improved performances for sulfur removal. Due to its tunable chemical structure, Cu-BTC has received wide interest in the structural modification.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The d-block metals and their cations can interact with sulfur compound molecules via π-complexation and adsorb them in facedown orientation on a flat surface, which helps achieve an excellent adsorption capability . The most prominent metal ions for π-complexation are Cu­(I) and Ag. , …”
Section: Introductionmentioning
confidence: 99%
“…Among the various desulfurization methods, ADS is a highly efficient technology with milder operating conditions, 14,15 more energy conservation than HDS, and lower investment than ODS. 16 The process of ADS includes fixed bed, 17 simulated moving bed, and batch adsorption 18 systems. The essential issue of ADS is to develop high-performance adsorbents with high adsorption capacities, acceptable selectivity, and excellent regeneration performance.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various desulfurization methods, ADS is a highly efficient technology with milder operating conditions, , more energy conservation than HDS, and lower investment than ODS . The process of ADS includes fixed bed, simulated moving bed, and batch adsorption systems.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on its production source and the stage of the upgrading process, biogas can contain a number of sulfur compounds that have the capability to corrode processing equipment and gas pipelines, to inhibit the performance of vehicle catalysts, and to damage fuel cells . Various researchers investigated the influence of sulfur compounds on fuel cell efficiency and concluded that sulfur compounds are the dominant poison . Since the extent and nature of cell degradation are linked to used cell materials and microstructural characteristics, the phenomenon of cell degradation cannot be generalized.…”
Section: Introductionmentioning
confidence: 99%